2021
DOI: 10.1038/s41598-021-89309-x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal ingestion of cocoa causes constriction of fetal ductus arteriosus in rats

Abstract: Maternal consumption of polyphenol-rich foods has been associated with fetal ductus arteriosus constriction (DAC), but safety of chocolate exposure in fetal life has not been studied. This experimental study tested the hypothesis that maternal cocoa consumption in late pregnancy causes fetal DAC, with possible associated antioxidant effects. Pregnant Wistar rats, at the 21st gestational day, received by orogastric tube cocoa (720 mg/Kg) for 12 h, indomethacin (10 mg/Kg), for 8 h, or only water, before cesaren … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Unlike the aforementioned human studies, we found that fetal RSV exposure had no impact on blood flow through the DA, indicating that RSV may not be the polyphenol responsible DA closure in utero. This notion is supported by preclinical studies that have specifically shown the flavonoids within green tea (Zielinsky, Manica, et al, 2012 ) and cacao (Zielinsky et al, 2021 ) are capable of causing premature DA closure and have also demonstrated that alongside prostaglandin inhibition an impairment to fetal NO concentrations by polyphenols may be a key contributor (Bubols et al, 2014 ). Although, RSV has been shown to inhibit the arachidonic acid pathway and thus the formation of the prostaglandins that aid in keeping the DA patent (Meng et al, 2021 ), RSV through its potent activation of SIRT‐1 is also capable of enhancing NO synthesis (Li & Forstermann, 2009 ; Milne & Denu, 2008 ).…”
Section: Discussionmentioning
confidence: 92%
“…Unlike the aforementioned human studies, we found that fetal RSV exposure had no impact on blood flow through the DA, indicating that RSV may not be the polyphenol responsible DA closure in utero. This notion is supported by preclinical studies that have specifically shown the flavonoids within green tea (Zielinsky, Manica, et al, 2012 ) and cacao (Zielinsky et al, 2021 ) are capable of causing premature DA closure and have also demonstrated that alongside prostaglandin inhibition an impairment to fetal NO concentrations by polyphenols may be a key contributor (Bubols et al, 2014 ). Although, RSV has been shown to inhibit the arachidonic acid pathway and thus the formation of the prostaglandins that aid in keeping the DA patent (Meng et al, 2021 ), RSV through its potent activation of SIRT‐1 is also capable of enhancing NO synthesis (Li & Forstermann, 2009 ; Milne & Denu, 2008 ).…”
Section: Discussionmentioning
confidence: 92%
“…During ductal closure, there are higher prostacyclin levels in smooth muscle cells at the sites of intimal thickening. The metabolic prostaglandin cascade, starting with arachidonic acid, plays a fundamental role in ductal patency, and its inhibition may lead to ductal constriction and related consequences, as has been reported after maternal ingestion of non-steroidal anti-inflammatory drugs or polyphenol-rich foods [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] . The present study suggests that neither prostaglandin inhibition nor alteration in ductal flow occurs as a consequence of DHA administration at a clinically recommended dose 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Patency of the ductus arteriosus is dependent on the presence of circulating prostaglandins, especially in the third trimester. Maternal consumption of substances, such as non-steroidal anti-inflammatory agents and polyphenol-rich foods, which have the ability to interfere with the metabolic pathway of prostaglandins, for example by inhibition of cyclo-oxygenase-2 activity or arachidonic acid metabolism, may exert a constrictive effect on the fetal ductus arteriosus [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] . The same metabolic pathway has been demonstrated as the basis for the anti-inflammatory effect of DHA 13 , but its effect on ductal patency has not yet been explored.…”
Section: Introductionmentioning
confidence: 99%
“…Ductal constriction (DC) is associated with maternal exposure to prostaglandin synthase inhibitors such as non-steroidal anti-inflammatory drugs (NSAIDs) in many published cases. In recent years, excessive polyphenol-rich food (PRF) consumption during pregnancy has also been reported to be associated with DC (3)(4)(5)(6). DC causes fetal blood flow redistribution, leading to increased pulmonary artery pressure and pulmonary resistance (7,8).…”
Section: Introductionmentioning
confidence: 99%